Recovery of Ammonia in Raw and Co-digested Swine Manure Using Gas-Permeable Membrane Technology - Oliveira Filho, Jose de Souza; Daguerre-Martini, Silvana; Vanotti, Matias B.; Saez-Tovar, Jose; Rosal, Antonio; Perez-Murcia, Maria D.; Bustamante, Maria A.; Moral, Raul (Frontiers in Sustainable Food Systems, 2018)
Anaerobic digestion of agro-industrial and livestock waste generates considerable digestate volumes that are important sources of nitrogen (N). However, on some occasions, the high concentrations of N present in the digestates may represent an obstacle to its use locally as fertilizer, since it can cause an environmental impact (European Community, 2000). This study analyzes the efficiency of gas-permeable membranes (GPM) in the recovery of the ammoniacal nitrogen (NH4+) present in the swine manure (SM, Control) and three digestates generated from the anaerobic co-digestion of mixtures of SM, fruit and vegetable sludge (FVS) from the vegetable industry (peppers and artichokes), and by-products of the tomato processing industry (TW) (skins and seeds), which were mixed at three different proportions [TW + FVS]: [SM]. Their NHx+ content was 2,240 mg L−1 for the SM and 4,670–5,370 for the digestate mixtures. Throughout the duration of the Necovery experiment (96 h), the percentages of NH4+ removal and recovery achieved were consistent among treatments, approximatelly 78 and 96%, respectively. The recovery of NH4+ for the digestate mixtures seems to be dependent on the treatment time, since the potential of N recovery was higher when the treatment time increased. However, for the control experiment (SM), with lower N concentration, the maximum N recovery was obtained at the experimental time established, without increasing the treatment time.